Firm performance and condensed corporate governance mechanism: Evidence of Nigerian financial institutions - Alex Adegboye; Stephen Ojeka; Kofo Adegboye; Emmanuel Ebuzor; Dayo Samson (Verslas: Teorija ir praktika / Business: Theory and Practice, 2019)
This paper extends the prior studies on corporate performance by empirically exploring the impact of overall corporate governance structure on firm performance. To unveil the objective of this study, firstly corporate governance index is built using Principal Component Analysis with 6 (six) identified corporate governance mechanisms from prior studies and then examines its effect on firms' performance. This study draws a sample of twenty-four (24) financial companies from the listed financial institutions in Nigeria for the period of 2013-2017. The formulated hypotheses are tested by employing static panel data estimators that are Fixed effect and Random Effect Regression. The results reveal that while controlling for firms' characteristics, constructed corporate governance indicator has a significant and negative influence on the firm performance measured by Return on Asset and Return on Equity. This finding supports that larger board, larger board committees and significant executive involvement have a detrimental influence on the performance of firms. The result implies a weak corporate governance structure is detrimental to higher financial performance amidst the weak institutions characterized in Nigeria context. That is, weaker corporate governance exhibits lower financial performance. This study then recommends that the corporate governance structure in Nigeria listed firms should be review with the intention to enhance the firm performance. Furthermore, it encourages the regulatory agencies like Central Bank of Nigeria, National Insurance Commission and Securities and Exchange Commission, to monitor the compliance of the listed firms to good governance endeavour.
Keywords: G32; G34; M14; M42; 650; Corporate governance index; return on equity; return on asset; principal component analysis